Electrostatics and viscosity are strongly linked in concentrated antibody solutions - Camerin, Fabrizio ; 0000-0003-2468-9351; Polimeni, Marco; Stradner, Anna; Zaccarelli, Emanuela; Schurtenberger, Peter ; 0000-0002-2790-8831 (Proceedings of the National Academy of Sciences of the United States of America, 2025)
Monoclonal antibodies are among the most promising therapeutic agents in modern medicine, yet their formulation into high-concentration solutions for subcutaneous self-administration poses a major challenge. A key obstacle is the marked increase in viscosity often observed under these conditions. To gain deeper insights into this phenomenon, coarse-grained models derived from soft matter physics have been widely employed. However, these models have yet to be fully leveraged for analyzing the rheological collective properties of such systems. In this study, using molecular dynamics simulations, we directly compute the antibody solution viscosity by starting from commonly used models in which electrostatic interactions are treated through effective screened Coulomb potentials. We demonstrate that this approach fails to reproduce experimental evidence and we show, by analyzing stress correlations in the system, that it is necessary to treat the heterogeneously charged domains with explicit Coulomb interactions, also including counterions and salt ions. By thoroughly analyzing the microscopic structure of the system, we further reveal the presence of transient strongly correlated antibodies which would not be present if charges were treated implicitly, thus pointing to a prominent role of electrostatics in determining the increase in viscosity at high concentrations. By taking advantage of our realistic treatment, new approaches can be devised to ensure that antibody solutions exhibit the desired characteristics for their intended broad use and effective deployment.
Keywords: antibodies; charge heterogeneity; coarse-grained modeling; explicit ions; viscosity